Evaluation of systemic and mucosal anti-HPV16 and anti-HPV18 antibody responses from vaccinated women - Kemp, Troy J. (2008)
Ideal methods to monitor HPV neutralizing antibodies induced by vaccination have not been established yet. Here, we evaluated systemic and cervical antibody levels induced by HPV16/18 AS04-adjuvanted vaccine (GlaxoSmithKline Biologicals) using a secreted alkaline phosphatase neutralization assay (SEAPNA) and enzyme-linked immunosorbent assay (ELISA). Serum and cervical secretions from 50 vaccinated women were used to assess (1) overall assay reproducibility; (2) inter-assay and inter-specimen correlation; (3) correlations between month 1 and month 12 titers. Strong correlations between SEAP-NA and ELISA were observed (serum anti-HPV16/18, = 0.91/0.85; cervix anti-HPV16/18, = 0.84/0.89). Systemic and cervical antibody measures also correlated well (range: 0.64–0.75); except at mid-cycle (range: 0.28–0.65). Correlations between antibody levels at 1 and 12 months following the start of vaccination were poor (range: 0.16–0.38). In conclusion, HPV16/18 VLP-based ELISA is a reliable and valid method to monitor anti-HPV16/18 neutralizing potential for the first year following vaccination; however, additional studies will be required to better define the effects of the time on cycle and patterns of antibody response over time following vaccination. © 2008 Elsevier Ltd. All rights reserved.